P-D12 Differential sensitivity of HIV-1 isolates to inhibition by mannose-binding lectins reveals the heterogeneity of the virus envelope glycosylation. (January 2016) - Peer, Muzafar; Upadhyay, Chitra; Arora, Sunil
Abstract : HIV envelope is densely coated with 18–33 potential N-linked glycans sites (PNGS), each differing in occupancy and composition affecting immunogenic and antigenic properties of the virus. Little is known about the heterogeneity in composition of these PNGS among different viruses. Using lectins with different oligosaccharide specificities, we studied the heterogeneity of the N-linked glycosylation present on HIV-1 Env. We studied 4 HIV-1 viruses SF162, BaL, JRFL, REJO with PNGS ranging from 25 to 29. The viruses showed distinct sensitivity to GNA and HHA with median IC50 values ranking as, SF162<BAL<JRFL<REJO implying that these viruses display glycans with different levels/types of mannose residues. When JRFL and REJO viruses were produced in the presence of glycosylation inhibitors kifunensine, swainsonine and 293S GnTI−/− cells, to produce homogenous N-glycans with mainly Man9-, Man9-5 + hybrid, and Man5- core, respectively, both viruses became similarly sensitive to GNA and HHA. To further delineate the mannose composition of these viruses, we used lectins which bind to different branches of Man5-9GlcNAc2 core present on the HIV Env: (1) GRFT binds to the terminal manα1-2man arms, (2) SV-N binds to the D3 arm, and (3) CV-N requires the D1 arm. In comparison to REJO, JRFL was highly sensitive to these lectins, with GRFT being most sensitive followed by CV-N and SV-N. However, viruses produced in the presence of glycosidase inhibitors were similarly sensitive to these lectins. None of the viruses were inhibited by PHA-E and LCA lectins which recognize only galactosylated glycans confirming that HIV has mostly high mannose type glycans. Overall, our data demonstrates that HIV-1 isolates display different sensitivity to lectins due in part to the microheterogeneity of N-linked glycans expressed on the Env of these isolates.